Smart Electrospun Nanofibers for Controlled Drug Release: Recent Advances and New Perspectives - Weng, Lin; Xie, Jingwei (Current Pharmaceutical Design, 2015)
In biological systems, chemical molecules or ions often release upon certain conditions, at a specific location, and over a desired period of time. Electrospun nanofibers that undergo alterations in the physicochemical characteristics corresponding to environmental changes have gained considerable interest for various applications. Inspired by biological systems, therapeutic molecules have been integrated with these smart electrospun nanofibers, presenting activation-modulated or feedback-regulated control of drug release. Compared to other materials like smart hydrogels, environment-responsive nanofiber-based drug delivery systems are relatively new but possess incomparable advantages due to their greater permeability, which allows shorter response time and more precise control over the release rate. In this article, we review the mechanisms of various environmental parameters functioning as stimuli to tailor the release rates of smart electrospun nanofibers. We also illustrate several typical examples in specific applications. We conclude this article with a discussion on perspectives and future possibilities in this field.
Keywords: controlled release